Etat Oceanographique De La Lagune De Oualidia, Maroc (2011-2012) - Makaoui, Ahmed; Idrissi, Mohammed; Agouzouk, Aziz; Larissi, Jamila; Baibai, Tarik; Ouehabi, Zineb El; Laamel, Mohamed Ait; Bessa, Ismail; Ettahiri, Omar; Hilmi, Karim (European Scientific Journal, ESJ, 2018)
The study of the Oualidia lagoon aims to establish the state of knowledge of the environment of this ecosystem after the construction of an inner dam in 2011 and the ecological functioning of the lagoon. For that, several campaigns were carried out between February 2011 and October 2012 and were the subject of a seasonal monitoring for the collection of the main biotic and abiotic parameters of the environment of this ecosystem. During the construction of the inner dam on 2011, a hydrological variability was marked in summer by low oxygen levels and maximum temperature variation between the two tides. Since the completion of the construction of the inner dam, there has been a significant increase in nutrients, mainly nitrogenous elements, and an increase in turbidity caused by an improvement in hydrodynamics, which has particularly increased of the sandpit modified the morphology and moved on south, creating a new main channel structure in 2011. This hydrodynamic was manifested on the upstream area by a decrease of the sedimentary organic matter due to the trapping of fine sediments in the inner dam. At the immediate level of the upstream area (Slikkes and Schorres), the hydrodynamic is relatively low, which has reduced the sedimentation rate on the upstream of the lagoon. The Oualidia lagoon is situated in a littoral zone influenced by the enrichment in deep cold waters loaded with nutritive salts, which invade it during the high tide, and would be, consequently after construction of the inner dam, protected from any confinement of the ecosystem.